(untitled) - Priest, Joseph (Reading, Massachusetts, 1991)
The fourth edition of Joseph Priest's Energy draws heavily on the experience of instructors who used earlier editions. It is designed for environmental science courses for non-science majors and is suitable for fulfilling their science requirement. The amount of quantitative material exposes students to the importance of quantitative reasoning without causing math anxiety. Priest has refined the physics and integrated it with energy issues, added new topics, updated the energy data, and included new exercises and problems. The fourth edition includes coverage of acid precipitation, the greenhouse effect, depletion of the ozone layer, and radon radioactivity in houses. The text furthers students' understanding with references that provide up-to-date sources of information and a guide to the types of publications and books students should examine; review sections with questions highlighting the main topics and ideas in the chapters as well as 25 multiple-choice questions and answers; and questions and problems sections that emphasize written answers and practical numerical calculations.
Keywords: Power (mechanics),Power resources